2023
DOI: 10.1021/acschemneuro.2c00730
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Review on Potential Signaling Pathways Involving the Transfer of α-Synuclein from the Gut to the Brain That Leads to Parkinson’s Disease

Abstract: Parkinson’s disease is the second most prevalent neurological disease after Alzheimer’s. Primarily, old age males are more affected than females. The aggregates of oligomeric forms of α-synuclein cause the loss of dopaminergic neurons in the substantia nigra pars compacta. Further, it leads to dopamine shortage in the striatum region. According to recent preclinical studies, environmental factors like pesticides, food supplements, pathogens, etc. enter the body through the mouth or nose and ultimately reach th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 125 publications
0
7
0
Order By: Relevance
“…Considering the roles of alpha-synucleine aggregation and dopamine decline in PD [38], we studied these 48 genes in reference to alteration in transgenic expression of human α-Synuclein and behavioural assays that are governed by the dopamine-signalling pathway, to perform a screening of those genes that affect these parameters. Different studies have demonstrated that α-Synuclein aggregation might change the metabolite profiling in the gut [39]. A study conducted on monkeys showed significantly elevated levels of L-aspartic acid, p-hydroxyphenylacetic acid, and glyceric acid, hence our idea here was to see whether alteration in levels of these genes can affect the parameters of neurodegeneration or neuronal health.…”
Section: Discussionmentioning
confidence: 99%
“…Considering the roles of alpha-synucleine aggregation and dopamine decline in PD [38], we studied these 48 genes in reference to alteration in transgenic expression of human α-Synuclein and behavioural assays that are governed by the dopamine-signalling pathway, to perform a screening of those genes that affect these parameters. Different studies have demonstrated that α-Synuclein aggregation might change the metabolite profiling in the gut [39]. A study conducted on monkeys showed significantly elevated levels of L-aspartic acid, p-hydroxyphenylacetic acid, and glyceric acid, hence our idea here was to see whether alteration in levels of these genes can affect the parameters of neurodegeneration or neuronal health.…”
Section: Discussionmentioning
confidence: 99%
“…Growing evidence suggests that there are distinct olfactory and gastrointestinal pathologies in the early stage of PD, which can significantly impact social functioning [ 2 , 3 , 48 50 ]. However, early treatments for these pathologies in PD are rare.…”
Section: Discussionmentioning
confidence: 99%
“…Lewy bodies, comprised of aggregated pathological α-synuclein, are the histological hallmark of PD pathology, and have been demonstrated to trigger a chain of misfolding in healthy proteins, migrate from cell to cell in a prion-like fashion, and promote neu-rodegeneration and neuroinflammation [83,84]. There are multiple potential sites of initial pathological protein aggregation; the landmark Braak hypothesis posits that α-synuclein misfolding begins in the gut, migrates up the vagus nerve to the olfactory bulb, and spreads throughout DA neural circuitry to reach DA neurons in the SNpc [83,85]. In support of this theory, Lewy bodies have been identified in presymptomatic PD-patient intestine, and PD patients frequently report GI symptoms and anosmia decades prior to developing motor deficits [81,82,86].…”
Section: Parkinson's Diseasementioning
confidence: 99%